Pelatihan Kesiapan Kerja untuk Meningkatkan Career Adaptability pada Siswa SMK di Kabupaten Temanggung - Linqa Lasut; Enggar Putri Harjanti; Maria Prima Novita (Fakultas Psikologi Universitas Kristen Satya Wacana, 2024)
Data from the Central Statistics Agency (BPS) shows that vocational school graduates occupy the highest position in the unemployment rate. The problem found in several vocational schools in Temanggung is the lack of work readiness seen from career adaptability which is the individual's readiness to face predictable tasks and be able to participate in work roles and be able to adapt to unexpected situations that arise due to changes in conditions. work (Savickas, 2005). Therefore, To increase work readiness in vocational school students, a work readiness training program is needed to increase career adaptability in vocational school students in Temanggung Regency. The aim of this research is to determine the increase in the implementation of vocational school student employment readiness training programs. The method used is quantitative experimentation with a one group pretest-posttest design. The side technique used was a saturated sampling technique with 10 vocational school students as participants. Data analysis used the Wilcoxon Signed Rank test. The research results showed that the implementation of the work readiness training program was able to increase career adaptability in vocational school students (Z = -2.859 and sig = 0.004).